2014
DOI: 10.1186/s12933-014-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 ameliorates cardiac ischemia/reperfusion injury via caveolae and caveolins-3

Abstract: BackgroundExendin-4, an exogenous glucagon-like peptide-1 receptor (GLP-1R) agonist, protects the heart from ischemia/reperfusion injury. However, the mechanisms for this protection are poorly understood. Caveolae, sarcolemmal invaginations, and caveolins, scaffolding proteins in caveolae, localize molecules involved in cardiac protection. We tested the hypothesis that caveolae and caveolins are essential for exendin-4 induced cardiac protection using in vitro and in vivo studies in control and caveolin-3 (Cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Reductions in ROS by Ex-4 and GLP-1 in the protection of cardiomyocytes were also reported previously [53,54]. Nevertheless, it was in a pretreatment procedure, where Ex-4 and GLP-1 (9-36) protected the heart against hypoxic damage [55]. Similar protective effects by decreasing ROS levels were reported previously by our laboratory [56,57].…”
Section: Discussionsupporting
confidence: 84%
“…Reductions in ROS by Ex-4 and GLP-1 in the protection of cardiomyocytes were also reported previously [53,54]. Nevertheless, it was in a pretreatment procedure, where Ex-4 and GLP-1 (9-36) protected the heart against hypoxic damage [55]. Similar protective effects by decreasing ROS levels were reported previously by our laboratory [56,57].…”
Section: Discussionsupporting
confidence: 84%
“…Cav-3 is a major isoform of the caveolin family proteins to form cardiomyocyte caveolae [20], serving as a platform to enrich cardioprotective signaling molecules, including PI3K/Akt [53] and JAK/STAT [54]. It has been reported that both caveolae and caveolin-3 are critical for retaining myocardial tolerance to I/R injury [21, 55] and Cav-3 expression is also required for opioid induced cardioprotection [23]. Therefore, any alteration of Cav-3 expression in diabetes may be implicated in the compromised RPC-mediated cardioprotection, and thus, restoring Cav-3 expression should be beneficial to preserve the effectiveness of RPC in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether AS-1 mediated protection against H/R-induced cell injury was through the caveolae dependent mechanism, we treated the cells with methyl-β-cyclodextrin (MCD) in order to disrupt caveolae 13 before the cells were treated with AS-1. Figure 7A and B showed disruption of caveolae by MCD abolished AS-1-induced protection against H/R-induced injury in H9C2 cardiomyocytes: the levels of cell viability and LDH release in AS-1 plus MCD treated cells were comparable with H/R-stimulated cells.…”
Section: Resultsmentioning
confidence: 99%